They Sang and They Celebrated: The Women’s Celebration in 1 Samuel 18:7 - Firth, David G. (Bulletin for biblical research, 2023)
Following David’s defeat of Goliath, he is met by the local women who sang and danced as they celebrated the victory. This song shows important links to earlier women’s songs in the Old Testament, indicating an important tradition of teaching through song that was passed down. First Samuel then shows evidence of this pattern as the song is subsequently recited by men who have learned it from the women.